PEMBAURAN YANG TAK PERNAH SELESAI - Rochmawati, Rochmawati (P2KK LIPI, 2004)
Ethnic cohesion in the Indonesian context is still problematic. Religions, political, and legal approuches could be utilised to achieve that cohesion. However, democratic and just society could only be achieved if there is political will to establish egalitarian society through applying equality before law among all ethnic groups.